2006
DOI: 10.1007/s00213-006-0358-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased frontal and paralimbic activation following ayahuasca, the pan-amazonian inebriant

Abstract: Rationale: Ayahuasca is a South American psychoactive plant tea which contains the serotonergic psychedelic N,N-dimethyltryptamine (DMT) and monoamine-oxidase inhibitors that render DMT orally active. Previous investigations with ayahuasca have highlighted a psychotropic effect profile characterized by enhanced introspective attention, with individuals reporting altered somatic perceptions and intense emotional modifications, frequently accompanied by visual imagery. Despite recent advances in the study of aya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
198
1
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 200 publications
(237 citation statements)
references
References 36 publications
21
198
1
17
Order By: Relevance
“…Psychedelics may alter thalamocortical transmission by stimulating 5-HT 2A receptors located in several key components of the CSTC loops Geyer and Vollenweider, 2008). This interpretation is consistent with the neuroimaging studies showing that oral administration of psilocybin, mescaline, and DMT alter neuronal activity during their peak effects in the frontomedial and frontolateral cortices ("hyperfrontality"), basal ganglia, and thalamus (Hermle et al, 1992(Hermle et al, , 1998Gouzoulis-Mayfrank et al, 1999;Riba et al, 2006), variously correlating with different dimensions of psychedelic states (Vollenweider and Geyer, 2001).…”
Section: Use As Tools To Study Brain Function and Connectivitysupporting
confidence: 77%
See 1 more Smart Citation
“…Psychedelics may alter thalamocortical transmission by stimulating 5-HT 2A receptors located in several key components of the CSTC loops Geyer and Vollenweider, 2008). This interpretation is consistent with the neuroimaging studies showing that oral administration of psilocybin, mescaline, and DMT alter neuronal activity during their peak effects in the frontomedial and frontolateral cortices ("hyperfrontality"), basal ganglia, and thalamus (Hermle et al, 1992(Hermle et al, , 1998Gouzoulis-Mayfrank et al, 1999;Riba et al, 2006), variously correlating with different dimensions of psychedelic states (Vollenweider and Geyer, 2001).…”
Section: Use As Tools To Study Brain Function and Connectivitysupporting
confidence: 77%
“…To examine the neural correlates of acute ayahuasca effects, Riba et al (2006) used single-photon emission tomography to study regional CBF after acute administration of ayahuasca to 15 healthy volunteers. Ayahuasca administration led to bilateral activation of the anterior insula/inferior frontal gyrus, with greater intensity seen in the right hemisphere.…”
Section: Use As Tools To Study Brain Function and Connectivitymentioning
confidence: 99%
“…Although nonsignificant, in the present study these effects were observed during a period ranging from 80 to 140 min after AYA administration, which is the time point when the subjective effects of AYA are peaking, as are DMT plasma levels. [8][9][10][11][12] The absence of statistically significant effects on BPRS-TD scores could be explained by the DMT concentration found in our AYA batch (0.08 mg/mL), which is lower than DMT doses used in previous studies that reported significant psychotropic effects of AYA (0.53 mg/ mL DMT). 9,12 The nonsignificant effects of AYA on the BPRS-TD subscale suggest that changes in sensory perception and thought content may not be essential for therapeutic effects.…”
Section: Discussionmentioning
confidence: 62%
“…6,[8][9][10][11] The psychoactive effects of AYA are produced by a combined action of peripheral (gastrointestinal and liver) monoamine oxidase A (MAO-A) inhibition by harmine and central 5-HT 1A/2A/2C agonist action of DMT on frontal and paralimbic brain areas. 8,9,12 Studies conducted among long-term (i.e., years or decades) members of religious groups that use AYA ritually suggest that this population does not present evidence of psychological, neuropsychological, or psychiatric harm caused by AYA. [13][14][15] In fact, there are several reports describing reduced mental health problems in AYA users.…”
Section: Introductionmentioning
confidence: 99%
“…Self-report questionnaires demonstrated somatic, perceptual and cognitive modifications, together with increases in positive mood and activation (Riba et al 2003). Electroencephalography measures during wakefulness indicated reductions in slow (delta and theta) and alpha-2 activity (Riba et al 2002) and measures of regional cerebral blood flow showed increased perfusion in paralimbic and frontal brain regions (Riba et al 2006). Sleep disturbances have been described for recreational drugs acting on serotonergic neurotransmission, such as 3,4 methylenedioxymethamphetamine (Morgan 2000).…”
Section: Introductionmentioning
confidence: 99%